Transparent heat-insulating coating based on up-conversion luminescent nanoparticles as well as preparation method and application of transparent heat-insulating coating
By using up-converting luminescent nanoparticles in nanothermal insulation coatings, combined with zinc oxide, tin oxide, gallium oxide, ytterbium oxide and erbium oxide, the existing nanothermal insulation coatings have been solved, and the efficient, economical and environmentally friendly transparent insulation effect is achieved.
Patent Information
- Application Number
- CN202411723816.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-28
AI Technical Summary
The existing nano-thermal insulation coatings have problems such as poor thermal insulation effect, short service life, cumbersome preparation processes, high costs and environmental pollution.
A transparent thermal insulation coating based on upconversion luminescent nanoparticles is used to form an efficient light conversion material to enhance the transparent thermal insulation performance of the coating by combining materials such as zinc oxide, tin oxide, gallium oxide, ytterbium oxide and erbium oxide.
It has achieved a significant improvement in the light-transmitting and thermal insulation performance of the coating, extended the service life, simplified the preparation process, reduced costs, and reduced environmental pollution.
Smart Images

Figure CN119529569A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of inorganic polymer materials, and in particular relates to an up-conversion luminescent coating and a preparation method and application thereof. Background Art
[0002] Glass is widely used in places with high lighting requirements, such as high-rise buildings, transparent ceilings, cars, exhibition halls, etc. Since ordinary glass has low selective transmittance to the solar spectrum, while visible light is transmitted, the energy in the infrared region of the solar spectrum also penetrates the glass in large quantities, causing the temperature in the room or car to rise, increasing the working time and load of the air conditioner or fan, thereby causing waste of electricity and other energy resources. To solve this problem, people have invented heat-reflective glass, hollow glass, and heat-reflective glass film, but these products have defects such as poor thermal insulation effect, low visible light transmittance, and high price and cost, which hinders the application and promotion of the products. Therefore, it is of great practical significance and broad market prospects to study a transparent thermal insulation coating with good light transmission and heat insulation performance and relatively low price and cost.
[0003] Nano coatings refer to materials added to coatings that contain nanoparticles, which can be functional fillers, surfactants, dispersants, defoamers and other modifiers. Their particle size reaches the nanometer level, so the coating is given a nanometer modification limit. Compared with ordinary coatings, nano coatings have more excellent special properties due to the nanometer effect of particles. Nano transparent thermal insulation coatings refer to the addition of powders with thermal insulation characteristics to the coating, making it thermally insulating and transparent to visible light. Due to the extensive use of glass in buildings, energy conservation through this approach can improve the living and working environment of human beings, reduce energy consumption to a certain extent, and will surely have broad market application prospects and receive strong support from the country.
[0004] In recent years, corresponding results have been achieved in the research of nano-transparent thermal insulation coatings. Zhao Shilin and others successfully prepared nano-ATO and ITO transparent thermal insulation coatings, which have excellent transmittance in the visible light region and can effectively block thermal radiation in the infrared light region (Zhang Yongjin, Zhao Shilin. Research and development of polyurethane nano-ATO transparent thermal insulation coatings [J]. Green Building, 2004, 20 (6): 18-19). Meng Qinglin and others dispersed nano-ATO in ethanol solution, mixed it with water-based polyurethane to make it fully dispersed, and then used a certain process to make them into thermal insulation coatings (Preparation of nano-ATO powder and study of its electro-optical and thermal properties [J]. New Building Materials).
[0005] However, current nano thermal insulation coatings are generally physical thermal insulation, that is, these nanoparticles achieve thermal insulation by reflecting thermal radiation in sunlight while allowing visible light to pass through. Often, the presence of these nanoparticles will affect the light transmittance of the coating, and it is easy to age and fall off due to long-term radiation such as ultraviolet rays, resulting in poor thermal insulation effect and short service life. In addition, the preparation process is cumbersome, costly, and polluting the environment. Therefore, it is urgent to find a new nano coating to increase the light transmittance and thermal insulation capacity of the glass. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention discloses a transparent heat-insulating glass coating made of a new, high-performance functional filler (upconversion luminescent material) to eliminate various defects of traditional coatings as much as possible and expand the application scope of the transparent heat-insulating glass coating.
[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0008] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100-150 parts of base coating, 5-10 parts of dispersing aid, and 0.5-3 parts of up-conversion luminescent nanoparticles.
[0009] Furthermore, the base coating is one or more of waterborne polyurethane, waterborne epoxy resin varnish and single-component silica coating.
[0010] Furthermore, the base coating is a single-component silicon dioxide coating.
[0011] The base coating of the present invention can be commercially available. The raw materials used in the embodiments of the present invention, including water-based polyurethane, were purchased from Anhui Dawei Huatai New Material Technology Co., Ltd., model AH-1704B-2. Water-based epoxy resin varnish was purchased from Shenzhen Borui Technology Co., Ltd., model BH-WEP-1050. Single-component silica coating was purchased from Changzhou Naroko New Material Technology Co., Ltd., model NC404.
[0012] Furthermore, the dispersing aid is one or more of a light stabilizer, a promoter, a defoaming agent, and an antioxidant.
[0013] Furthermore, the light stabilizer is 1-methyl-8-(1,2,2,6,6-pentamethyl-4-piperidine) sebacate; the defoamer is a silicone emulsion defoamer; the accelerator is one of stearyl phosphate betaine, lauryl phosphate betaine, lauryl dimethyl amine oxide, and cocoamidopropyl dimethyl amine oxide; and the antioxidant is pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate.
[0014] Furthermore, the upconversion luminescent nanoparticles include structural functional components and upconversion luminescent components, and the mass ratio of the structural functional components and the upconversion luminescent components is 1:1.
[0015] Furthermore, the structural functional components are zinc oxide ZnO, tin oxide SnO, and gallium oxide Ga2O3, and the mass ratio of the three is 1:0.5:1; the up-conversion luminescent components are ytterbium oxide Yb3O4 and erbium oxide Er2O3, and the mass ratio of the two is 1:2.
[0016] A method for preparing a transparent heat-insulating coating based on upconversion luminescent nanoparticles comprises the following preparation steps:
[0017] (1) mixing the structural and functional components zinc oxide ZnO, tin oxide SnO, gallium oxide Ga2O3 and the up-conversion luminescent components ytterbium oxide Yb3O4 and erbium oxide Er2O3 in proportion, adding the mixture into a grinding container, adding water, grinding and mixing to obtain a mixed powder;
[0018] (2) After the mixed powder is dried, pre-sintering is performed. The pre-sintering method is sintering at 500-600° C. for 2-3 hours in an air atmosphere;
[0019] (3) The pre-sintered mixed powder is subjected to high-temperature sintering. The high-temperature sintering method is to increase the temperature to 800-850°C at a heating rate of 10°C / min and keep it at this temperature for 3-4 hours; then increase the temperature to 1150-1200°C at a heating rate of 5°C / min and keep it at this temperature for 5-6 hours, and finally cool it down naturally to obtain upconversion luminescent nanoparticles;
[0020] (4) grinding the upconversion luminescent nanoparticles obtained in step (3) for a second time, mixing the base coating, the dispersing aid, and the upconversion luminescent nanoparticles after the second grinding according to weight, and continuously stirring and mixing until uniform, to obtain a final product coating.
[0021] Furthermore, the grinding time in step (1) is 0.5 h.
[0022] Furthermore, in step (2), the drying temperature is 90° C. and the drying time is 24 h.
[0023] An application of a transparent heat-insulating coating based on upconversion luminescent nanoparticles is used for coating the surface of glass, and transparent heat-insulating glass is obtained after drying and curing.
[0024] In traditional nano thermal insulation coatings, the inorganic nanoparticles added usually reduce the absorption of heat by reflecting sunlight and infrared rays. Or, inorganic particles are filled in the coating to form a closed porous structure. These structures can serve as a barrier to heat transfer and prevent the formation of "thermal bridges", thereby improving the overall thermal insulation performance of the coating. Based on this principle, it is usually necessary to add more inorganic particles to the coating. On the one hand, the addition of too many inorganic particles will affect the light transmittance of the coating. In order to improve the infrared reflectivity, some nano thermal insulation coatings often sacrifice light transmittance, which will greatly limit their use in some fields with high light transmittance requirements. On the other hand, if too many nanoparticles are added, the dispersion stability is poor and agglomeration is prone to occur, resulting in a decrease in the transparency and thermal insulation performance of the coating. Therefore, traditional nano coatings have not been efficiently utilized in many fields.
[0025] Therefore, the applicant thought of changing the traditional inorganic nanoparticles and using zinc oxide ZnO, tin oxide SnO, gallium oxide Ga2O3, ytterbium oxide Yb3O4 and erbium oxide Er2O3 as functional components to cooperate with each other to construct a light-transmitting and heat-insulating coating with a low amount of nanoparticles added.
[0026] Among them, gallium oxide and zinc oxide can play a role of structural support on the one hand, providing structural support in the base material, enhancing the conductivity and photoelectric properties of the material, and at the same time, both tin oxide and gallium oxide have good infrared light reflection effect, effectively blocking heat transfer. On the other hand, zinc oxide is a wide bandgap semiconductor material with good UV resistance and infrared light reflection, which can improve the durability and mildew resistance of the coating and absorb ultraviolet radiation; after adding gallium, ZnO can be transformed into a moderate electrical conductor with the ability to reflect near-infrared light, thereby enhancing its thermal insulation performance. At the same time, high-temperature solid-phase reaction can form zinc gallium oxide ZnGa2O4. Both ZnO and ZnGa2O4 have high visible light transmittance and anti-ultraviolet radiation effect. The combination of the three can effectively transmit light and insulate while providing physical structural support.
[0027] Ytterbium oxide Yb3O4 and erbium oxide Er2O3 are used as upconversion luminescent components. The rare earth ion ytterbium ion (Yb) has a rich energy level structure and excellent optical properties. After being used in combination with erbium, the ytterbium ion acts as an activation center and can effectively transfer energy to the rare earth ion (erbium ion Er) by absorbing pump light (usually near-infrared light). 3 +), thereby generating visible light emission, converting low-energy photons (infrared light) into high-energy visible light, increasing visible light and reducing infrared light, effectively improving light transmittance and heat insulation performance.
[0028] Therefore, gallium oxide and zinc oxide provide structural support in the base material, enhancing the conductivity and photoelectric properties of the material, while ytterbium oxide and erbium oxide provide efficient light conversion. After equal proportions of the structural functional components and the upconversion luminescent components are mixed in the high-temperature solid phase, upconversion luminescent nanoparticles with multiple crystal structures coexisting are obtained. After being added to the base coating, they work synergistically to effectively improve the performance of the nanocoating and increase its light transmittance and heat insulation properties.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The present invention achieves a significant improvement in the light transmission and heat insulation performance of the coating by adding a small amount of upconversion nanoparticles to the coating, thereby expanding the application scope of upconversion materials, filling the gap in the research on the application of this material in the field of architectural coatings, and enriching the relevant theories of upconversion luminescent energy-saving coatings;
[0031] (2) Improve the performance of traditional transparent thermal insulation coatings through upconversion luminescent materials, promote technological progress in related industries and the vigorous development of the coatings industry. Promote the widespread use of transparent thermal insulation coatings and contribute to energy conservation and consumption reduction and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 XRD images of the coating prepared in Example 1 of the present invention and their corresponding standard PDF cards;
[0033] Figure 2 This is the FT-IR curve of the coating prepared in Example 1 of the present invention;
[0034] Figure 3 The heat insulation performance test results of Example 1, Examples 4-8 and the blank control glass sheet ck of the present invention are shown;
[0035] Figure 4 The thermal insulation performance test results of Example 1 of the present invention, Comparative Examples 1-9 and the blank control glass sheet ck are shown. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below in conjunction with specific embodiments, but is not limited thereto.
[0037] Example 1
[0038] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 0.5 parts of up-conversion luminescent nanoparticles.
[0039] The base coating is a single-component silicon dioxide coating.
[0040] The single-component silicon dioxide coating of this embodiment was purchased from Changzhou Naroko New Material Technology Co., Ltd., model number NC404.
[0041] The dispersing aid is a defoaming agent.
[0042] The defoamer is an organosilicon emulsion defoamer.
[0043] The upconversion luminescent nanoparticles include structural functional components and upconversion luminescent components, and the mass ratio of the structural functional components and the upconversion luminescent components is 1:1.
[0044] The structural functional components are zinc oxide ZnO, tin oxide SnO, and gallium oxide Ga2O3, and the mass ratio of the three is 1:0.5:1; the up-conversion luminescent components are ytterbium oxide Yb3O4 and erbium oxide Er2O3, and the mass ratio of the two is 1:2.
[0045] A method for preparing a transparent heat-insulating coating based on upconversion luminescent nanoparticles comprises the following preparation steps:
[0046] (1) mixing the structural and functional components zinc oxide ZnO, tin oxide SnO, gallium oxide Ga2O3 and the up-conversion luminescent components ytterbium oxide Yb3O4 and erbium oxide Er2O3 in proportion, adding the mixture into a grinding container, adding water, grinding and mixing to obtain a mixed powder;
[0047] (2) After the mixed powder is dried, pre-sintering is performed, and the pre-sintering method is sintering at 500° C. for 2 h in an air atmosphere;
[0048] (3) The pre-sintered mixed powder is subjected to high-temperature sintering. The high-temperature sintering method is to increase the temperature to 850°C at a heating rate of 10°C / min and keep it at this temperature for 3 hours; then increase the temperature to 1150°C at a heating rate of 5°C / min and keep it at this temperature for 5 hours, and finally cool it naturally to obtain up-conversion luminescent nanoparticles; the up-conversion luminescent nanoparticles obtained in this step are ground and dried, and 1g of the sample is taken out and labeled for XRD analysis to obtain the XRD diffraction spectrum. The results are as follows: Figure 1 As shown. Use Fourier infrared spectrometer to detect the infrared absorption of the sample and obtain the infrared absorption spectrum of the sample. The vertical axis represents the transmittance, which is used to measure the degree of transmittance of the sample to light of different wavelengths; the horizontal axis represents the wave number, and the higher the wave number, the shorter the wavelength. Figure 2 Display, 1000cm -1 The strongest absorption peak appears nearby, and this position belongs to the near-infrared spectral region. The appearance of the strongest absorption peak may be caused by the absorption of infrared light by the nanoparticles in the upconversion material, which is in line with the basic principle of upconversion luminescent materials.
[0049] (4) grinding the upconversion luminescent nanoparticles obtained in step (3) for a second time, mixing the base coating, the dispersing aid, and the upconversion luminescent nanoparticles after the second grinding according to weight, and continuously stirring and mixing until uniform, to obtain a final product coating.
[0050] The grinding time in step (1) is 0.5 h.
[0051] The drying temperature of step (2) is 90° C. and the drying time is 24 h.
[0052] An application of a transparent heat-insulating coating based on upconversion luminescent nanoparticles is used for coating the surface of glass, and transparent heat-insulating glass is obtained after drying and curing.
[0053] Example 2
[0054] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 150 parts of base coating, 10 parts of dispersing aid and 0.75 parts of up-conversion luminescent nanoparticles.
[0055] The base coating is waterborne polyurethane.
[0056] The raw materials used in this embodiment, including water-based polyurethane, were purchased from Anhui Dawei Huatai New Material Technology Co., Ltd., model AH-1704B-2.
[0057] The dispersing aid is a accelerator.
[0058] The accelerator is stearyl betaine phosphate.
[0059] The upconversion luminescent nanoparticles include structural functional components and upconversion luminescent components, and the mass ratio of the structural functional components and the upconversion luminescent components is 1:1.
[0060] The structural functional components are zinc oxide ZnO, tin oxide SnO, and gallium oxide Ga2O3, and the mass ratio of the three is 1:0.5:1; the up-conversion luminescent components are ytterbium oxide Yb3O4 and erbium oxide Er2O3, and the mass ratio of the two is 1:2.
[0061] A method for preparing a transparent heat-insulating coating based on upconversion luminescent nanoparticles comprises the following preparation steps:
[0062] (1) mixing the structural and functional components zinc oxide ZnO, tin oxide SnO, gallium oxide Ga2O3 and the up-conversion luminescent components ytterbium oxide Yb3O4 and erbium oxide Er2O3 in proportion, adding the mixture into a grinding container, adding water, grinding and mixing to obtain a mixed powder;
[0063] (2) After the mixed powder is dried, pre-sintering is performed, and the pre-sintering method is sintering at 600° C. for 3 h in an air atmosphere;
[0064] (3) The pre-sintered mixed powder is subjected to high-temperature sintering. The high-temperature sintering method is to increase the temperature to 800°C at a heating rate of 10°C / min and keep it at that temperature for 4 hours; then increase the temperature to 1200°C at a heating rate of 5°C / min and keep it at that temperature for 6 hours, and finally cool it down naturally to obtain upconversion luminescent nanoparticles;
[0065] (4) grinding the upconversion luminescent nanoparticles obtained in step (3) for a second time, mixing the base coating, the dispersing aid, and the upconversion luminescent nanoparticles after the second grinding according to weight, and continuously stirring and mixing until uniform, to obtain a final product coating.
[0066] The grinding time in step (1) is 0.5 h.
[0067] Step (2) The drying temperature is 90°C and the drying time is 24h.
[0068] An application of a transparent heat-insulating coating based on upconversion luminescent nanoparticles is used for coating a glass surface, and transparent heat-insulating glass is obtained after drying and curing.
[0069] Example 3
[0070] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 120 parts of base coating, 6 parts of dispersing aid and 0.6 parts of up-conversion luminescent nanoparticles.
[0071] The base coating is a water-based epoxy resin varnish.
[0072] The water-based epoxy resin varnish used in this embodiment was purchased from Shenzhen Borui Technology Co., Ltd., model number BH-WEP-1050.
[0073] The dispersing aids are light stabilizers and antioxidants, and the mass ratio of the two is 1:1.
[0074] The light stabilizer is 1-methyl-8-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate; and the antioxidant is pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate.
[0075] The upconversion luminescent nanoparticles include structural functional components and upconversion luminescent components, and the mass ratio of the structural functional components and the upconversion luminescent components is 1:1.
[0076] The structural functional components are zinc oxide ZnO, tin oxide SnO, and gallium oxide Ga2O3, and the mass ratio of the three is 1:0.5:1; the up-conversion luminescent components are ytterbium oxide Yb3O4 and erbium oxide Er2O3, and the mass ratio of the two is 1:2.
[0077] A method for preparing a transparent heat-insulating coating based on upconversion luminescent nanoparticles comprises the following preparation steps:
[0078] (1) mixing the structural and functional components zinc oxide ZnO, tin oxide SnO, gallium oxide Ga2O3 and the up-conversion luminescent components ytterbium oxide Yb3O4 and erbium oxide Er2O3 in proportion, adding the mixture into a grinding container, adding water, grinding and mixing to obtain a mixed powder;
[0079] (2) After the mixed powder is dried, it is pre-sintered at 550° C. for 3 h in an air atmosphere;
[0080] (3) The pre-sintered mixed powder is subjected to high-temperature sintering. The high-temperature sintering method is to increase the temperature to 850°C at a heating rate of 10°C / min and keep it at that temperature for 3 hours; then increase the temperature to 1150°C at a heating rate of 5°C / min and keep it at that temperature for 5 hours, and finally cool it down naturally to obtain upconversion luminescent nanoparticles;
[0081] (4) grinding the upconversion luminescent nanoparticles obtained in step (3) for a second time, mixing the base coating, the dispersing aid, and the upconversion luminescent nanoparticles after the second grinding according to weight, and continuously stirring and mixing until uniform, to obtain a final product coating.
[0082] The grinding time in step (1) is 0.5 h.
[0083] Step (2) The drying temperature is 90°C and the drying time is 24h.
[0084] An application of a transparent heat-insulating coating based on upconversion luminescent nanoparticles is used for coating a glass surface, and transparent heat-insulating glass is obtained after drying and curing.
[0085] Example 4
[0086] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 1 part of up-conversion luminescent nanoparticles.
[0087] Compared with Example 1, this example is different in the amount of up-conversion luminescent nanoparticles used, while the other raw materials and preparation methods are the same as those of Example 1.
[0088] Example 5
[0089] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 1.5 parts of up-conversion luminescent nanoparticles.
[0090] Compared with Example 1, this example is different in the amount of up-conversion luminescent nanoparticles used, while the other raw materials and preparation methods are the same as those of Example 1.
[0091] Example 6
[0092] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 2 parts of up-conversion luminescent nanoparticles.
[0093] Compared with Example 1, this example is different in the amount of up-conversion luminescent nanoparticles used, while the other raw materials and preparation methods are the same as those of Example 1.
[0094] Example 7
[0095] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 2.5 parts of up-conversion luminescent nanoparticles.
[0096] Compared with Example 1, this example is different in the amount of up-conversion luminescent nanoparticles used, while the other raw materials and preparation methods are the same as those of Example 1.
[0097] Example 8
[0098] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 3 parts of up-conversion luminescent nanoparticles.
[0099] Compared with Example 1, this example is different in the amount of up-conversion luminescent nanoparticles used, while the other raw materials and preparation methods are the same as those of Example 1.
[0100] Comparative Example 1
[0101] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid, and 0.5 parts of structural functional components.
[0102] The structural functional components are zinc oxide ZnO, tin oxide SnO and gallium oxide Ga2O3, and the mass ratio of the three is 1:0.5:1.
[0103] In this comparative example, except that only structural and functional components are added, the remaining raw materials and preparation method are the same as those in Example 1.
[0104] Comparative Example 2
[0105] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 0.5 parts of up-conversion luminescent component.
[0106] The up-conversion luminescent components are ytterbium oxide Yb3O4 and erbium oxide Er2O3, with a mass ratio of 1:2.
[0107] In this comparative example, except that only up-conversion luminescent components are added, the rest of the raw materials and preparation methods are the same as those in Example 1.
[0108] Comparative Example 3
[0109] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 0.5 parts of up-conversion luminescent nanoparticles.
[0110] The upconversion luminescent nanoparticles include structural functional components and upconversion luminescent components, and the mass ratio of the structural functional components and the upconversion luminescent components is 1:1.
[0111] The structural functional components are tin oxide SnO and gallium oxide Ga2O3, with a mass ratio of 0.5:1; the up-conversion luminescent components are ytterbium oxide Yb3O4 and erbium oxide Er2O3, with a mass ratio of 1:2.
[0112] In this comparative example, except that zinc oxide is not added, the other raw materials and preparation method are the same as those in Example 1.
[0113] Comparative Example 4
[0114] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 0.5 parts of up-conversion luminescent nanoparticles.
[0115] The upconversion luminescent nanoparticles include structural functional components and upconversion luminescent components, and the mass ratio of the structural functional components and the upconversion luminescent components is 1:1.
[0116] The structural functional components are zinc oxide ZnO and gallium oxide Ga2O3, with a mass ratio of 1:1; the up-conversion luminescent components are ytterbium oxide Yb3O4 and erbium oxide Er2O3, with a mass ratio of 1:2.
[0117] In this comparative example, except that tin oxide is not added, the other raw materials and preparation method are the same as those in Example 1.
[0118] Comparative Example 5
[0119] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 0.5 parts of up-conversion luminescent nanoparticles.
[0120] The upconversion luminescent nanoparticles include structural functional components and upconversion luminescent components, and the mass ratio of the structural functional components and the upconversion luminescent components is 1:1.
[0121] The structural functional components are zinc oxide ZnO and tin oxide SnO, and the mass ratio of the three is 1:0.5; the up-conversion luminescent components are ytterbium oxide Yb3O4 and erbium oxide Er2O3, and the mass ratio of the two is 1:2.
[0122] In this comparative example, except that gallium oxide is not added, the other raw materials and preparation method are the same as those in Example 1.
[0123] Comparative Example 6
[0124] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 0.5 parts of up-conversion luminescent nanoparticles.
[0125] The upconversion luminescent nanoparticles include structural functional components and upconversion luminescent components, and the mass ratio of the structural functional components and the upconversion luminescent components is 1:1.
[0126] The structural functional components are zinc oxide ZnO, tin oxide SnO, and gallium oxide Ga2O3, and the mass ratio of the three is 1:0.5:1; the up-conversion luminescent component is ytterbium oxide Yb3O4.
[0127] In this comparative example, except that erbium oxide is not added, the other raw materials and preparation method are the same as those in Example 1.
[0128] Comparative Example 7
[0129] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 0.5 parts of up-conversion luminescent nanoparticles.
[0130] The upconversion luminescent nanoparticles include structural functional components and upconversion luminescent components, and the mass ratio of the structural functional components and the upconversion luminescent components is 1:1.
[0131] The structural functional components are zinc oxide ZnO, tin oxide SnO, and gallium oxide Ga2O3, and the mass ratio of the three is 1:0.5:1; the up-conversion luminescent component is erbium oxide Er2O3.
[0132] In this comparative example, except that ytterbium oxide is not added, the other raw materials and preparation method are the same as those in Example 1.
[0133] Comparative Example 8
[0134] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 0.5 parts of up-conversion luminescent nanoparticles.
[0135] The upconversion luminescent nanoparticles include structural functional components and upconversion luminescent components, and the mass ratio of the structural functional components and the upconversion luminescent components is 2:1.
[0136] The structural functional components are zinc oxide ZnO, tin oxide SnO, and gallium oxide Ga2O3, and the mass ratio of the three is 1:0.5:1; the up-conversion luminescent components are ytterbium oxide Yb3O4 and erbium oxide Er2O3, and the mass ratio of the two is 1:2.
[0137] In this comparative example, except for changing only the composition ratio of the structural functional component and the up-conversion luminescent component, the other raw materials and preparation method are the same as those in Example 1.
[0138] Comparative Example 9
[0139] A transparent heat-insulating coating based on up-conversion luminescent nanoparticles comprises the following raw materials in parts by weight: 100 parts of base coating, 5 parts of dispersing aid and 0.5 parts of up-conversion luminescent nanoparticles.
[0140] The upconversion luminescent nanoparticles include structural functional components and upconversion luminescent components, and the mass ratio of the structural functional components and the upconversion luminescent components is 1:2.
[0141] The structural functional components are zinc oxide ZnO, tin oxide SnO, and gallium oxide Ga2O3, and the mass ratio of the three is 1:0.5:1; the up-conversion luminescent components are ytterbium oxide Yb3O4 and erbium oxide Er2O3, and the mass ratio of the two is 1:2.
[0142] In this comparative example, except for changing only the composition ratio of the structural functional component and the up-conversion luminescent component, the other raw materials and preparation method are the same as those in Example 1.
[0143] Performance Testing
[0144] The coatings of the embodiment and the comparative example were used to manufacture nano transparent heat insulating glass. The specific method was: the heat insulating coating was applied to the glass surface by roller coating or flow coating, and allowed to stand for 24 hours to form a firm coating to prepare transparent heat insulating glass. When testing the spectral performance, the coating was applied to a 40mm×10mm×1mm glass sheet, and when testing the heat insulation and application performance, the coating was applied to a 400mm×400mm×5mm glass plate.
[0145] Spectral performance:
[0146] The transmittance of the coated glass sheet in the wavelength range of 200-4000nm was tested using a Lambda 750 UV-visible-near infrared spectrophotometer produced by PE Company of the United States.
[0147] Thermal insulation performance:
[0148] The blank glass plate and the coated glass plate were placed in an insulation foam box, and thermocouple thermometers were installed inside the insulation box (about 15 cm away from the glass plate) to measure the temperature change. The simulated heat source was a 500W iodine tungsten lamp, which was fixed above the insulation box, about 30 cm away from the glass plate, and the thermometer reading was recorded every 1 minute.
[0149] Application performance:
[0150] Observe the color and appearance of the coating with reference to GB / T1729-1979 "Determination of paint film color and appearance". Test the hardness and adhesion of the coated glass sheet with a film thickness of 1.2 mm according to GB / T6739-2006 "Determination of paint film hardness by pencil method for paints and varnishes" and GB / T1720-1979 "Determination of paint film adhesion". Soak the coated glass sheet (film thickness 1.2 mm) in (23±2)℃ distilled water for 24 hours according to GB / T1733-1993 "Determination of paint film water resistance" (Method A) and observe the coating. According to GB / T1735-2009 "Determination of heat resistance of paints and varnishes", put the glass sheet (film thickness 1.2 mm) into the oven and heat it to (100±2)℃ and keep it for 3 hours to observe whether the coating changes. The coating was placed in a laboratory and stored under natural conditions (temperature 18-35°C, humidity 40%-80%) for 6 months to observe whether there were obvious adverse conditions such as sedimentation or stratification, so as to judge its storage stability. Each group of experiments was repeated three times.
[0151] Table 1 Transmittance of different experimental groups
[0152] 1200nm near infrared light transmittance % 680nm visible light transmittance % 400nm near ultraviolet light transmittance% Example 1 50.1 81.0 22.6 Example 2 50.4 81.1 22.4 Example 3 50.3 81.2 22.4 Example 4 48.2 82.1 21.7 Example 5 46.1 83.5 20.6 Example 6 43.2 84.1 19.7 Example 7 42.1 84.8 19.2 Example 8 41.5 85.2 18.8 Comparative Example 1 58.2 70.3 65.5 Comparative Example 2 57.5 72.4 69.8 Comparative Example 3 55.1 74.5 45.4 Comparative Example 4 54.8 74.9 42.2 Comparative Example 5 55.0 74.3 43.5 Comparative Example 6 54.8 74.0 40.0 Comparative Example 7 54.5 73.5 38.8 Comparative Example 8 53.2 75.2 30.1 Comparative Example 9 53.0 75.5 28.9 Blank Glass 89.5 88.6 89.8
[0153] From the data in Table 1, we can see that the coating obtained in the embodiment of the present invention has a visible light transmittance of more than 80%, and can effectively shield and absorb near-infrared and near-ultraviolet light. However, in the comparative examples 1-9 in which the functional nanoparticles are changed, the synergistic effect between the components is weakened or disappears, and the light conversion and shielding effect is weakened, thus resulting in weakened performance. Figure 3-4 From the test results of the thermal insulation performance of each experimental group, we can also see that the performance of the paint film in the comparative group also shows a weakening trend compared with the embodiment.
[0154] In terms of the application performance of the paint film, the paint of the embodiments of the present invention and the comparative example, after being coated on the glass surface and air-dried, is transparent, has a smooth surface, a pencil hardness of B, and an adhesion of 2. After being soaked in distilled water for 2 hours and dried with filter paper, the appearance of the three test plates prepared by the same process showed no obvious discoloration, bubbles, or shedding. After being placed in a forced air drying oven at (100±2)℃ for 3 hours, the paint film showed no obvious wrinkling, shedding, or discoloration. There was no obvious sediment at the bottom of the paint after it was placed for 6 months. The change of functional nanoparticles has no significant effect on the application performance of the paint film.
[0155] It should be noted that the above embodiments are only partial embodiments of the preferred methods of implementing the present invention, rather than all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
Claims
1. A transparent heat-insulating coating based on upconversion luminescent nanoparticles, characterized in that: The invention comprises the following raw materials in parts by weight: 100-150 parts of base coating, 5-10 parts of dispersing aid and 0.5-3 parts of up-conversion luminescent nanoparticles.
2. The transparent heat-insulating coating based on upconversion luminescent nanoparticles according to claim 1, characterized in that: The base coating is one or more of waterborne polyurethane, waterborne epoxy resin varnish and single-component silicon dioxide coating.
3. The transparent heat-insulating coating based on upconversion luminescent nanoparticles according to claim 2, characterized in that: The base coating is a single-component silicon dioxide coating.
4. The transparent heat-insulating coating based on upconversion luminescent nanoparticles according to claim 1, characterized in that: The dispersing aid is one or more of a light stabilizer, a accelerator, a defoamer, and an antioxidant.
5. The transparent heat-insulating coating based on upconversion luminescent nanoparticles according to claim 1, characterized in that: The light stabilizer is 1-methyl-8-(1,2,2,6,6-pentamethyl-4-piperidinyl) sebacate; the defoamer is a silicone emulsion defoamer; the accelerator is one of stearyl phosphate betaine, lauryl phosphate betaine, lauryl dimethyl amine oxide, and cocoamidopropyl dimethyl amine oxide; and the antioxidant is pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate.
6. The transparent heat-insulating coating based on upconversion luminescent nanoparticles according to claim 1, characterized in that: The upconversion luminescent nanoparticles include structural functional components and upconversion luminescent components, and the mass ratio of the structural functional components and the upconversion luminescent components is 1:
1.
7. The transparent heat-insulating coating based on up-conversion luminescent nanoparticles according to claim 6, characterized in that: The structural functional components are zinc oxide ZnO, tin oxide SnO, and gallium oxide Ga2O3, and the mass ratio of the three is 1:0.5:1; the up-conversion luminescent components are ytterbium oxide Yb3O4 and erbium oxide Er2O3, and the mass ratio of the two is 1:
2.
8. A method for preparing a transparent heat-insulating coating based on up-conversion luminescent nanoparticles according to any one of claims 1 to 7, characterized in that: The method comprises the following preparation steps: (1) mixing the structural and functional components zinc oxide ZnO, tin oxide SnO, gallium oxide Ga2O3 and the up-conversion luminescent components ytterbium oxide Yb3O4 and erbium oxide Er2O3 in proportion, adding the mixture into a grinding container, adding water, grinding and mixing to obtain a mixed powder; (2) After the mixed powder is dried, pre-sintering is performed. The pre-sintering method is sintering at 500-600° C. for 2-3 hours in an air atmosphere; (3) The pre-sintered mixed powder is subjected to high-temperature sintering. The high-temperature sintering method is to increase the temperature to 800-850°C at a heating rate of 10°C / min and keep it at this temperature for 3-4 hours; then increase the temperature to 1150-1200°C at a heating rate of 5°C / min and keep it at this temperature for 5-6 hours, and finally cool it down naturally to obtain upconversion luminescent nanoparticles; (4) grinding the upconversion luminescent nanoparticles obtained in step (3) for a second time, mixing the base coating, the dispersing aid, and the upconversion luminescent nanoparticles after the second grinding according to weight, and continuously stirring and mixing until uniform, to obtain a final product coating.
9. An application of a transparent heat-insulating coating based on up-conversion luminescent nanoparticles according to any one of claims 1 to 7, characterized in that: Used for coating on glass surface, transparent heat-insulating glass is obtained after drying and curing.
Citation Information
Patent Citations
Up-conversion material based on tin antimony oxide
CN106987248A
Near infrared up-conversion long afterglow luminescent material and preparation method thereof
CN107286932A
Nanometer up-conversion long-lasting luminescent material and preparation method and application thereof
CN108753288A
High-performance water-based luminescent coating
CN117844317A
Coating composition having polysilazane and wavelength converting agent and wavelength converting sheet prepared using the same
US20150232745A1
Cited By
Nano GTO-hyperbranched polyurethane urea transparent heat-insulation self-cleaning coating and preparation method thereof
CN121930726A